2015
DOI: 10.1002/ijc.29392
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin d synthase is a potential novel therapeutic agent for the treatment of gastric carcinomas expressing PPARγ

Abstract: The antitumor activity of prostaglandin (PG) D 2 has been demonstrated against some types of cancer, including gastric cancer. However, exogenous PGD 2 is not useful from a clinical point of view because it is rapidly metabolized in vivo. The aim of this study was to clarify the antitumor efficacy of an alternative, PGD synthase (PGDS), on gastric cancer cells. The effects of PGD 2 and PGDS on the proliferation of gastric cancer cells were examined in vivo and in vitro. The expression levels of PGD 2 receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Subsequent studies have confirmed that PGD2 metabolite 15‐deoxy‐Δ12–14‐PGJ2 suppressed cell growth and induced apoptosis in GC cell lines . Overexpression of PGD synthase decreased the proliferation of GC cells dependent on PPARγ signaling . All of these studies have demonstrated that PGD2 has the ability to inhibit cell growth and is an important potential target for anti‐GC treatments.…”
Section: Discussionmentioning
confidence: 79%
“…Subsequent studies have confirmed that PGD2 metabolite 15‐deoxy‐Δ12–14‐PGJ2 suppressed cell growth and induced apoptosis in GC cell lines . Overexpression of PGD synthase decreased the proliferation of GC cells dependent on PPARγ signaling . All of these studies have demonstrated that PGD2 has the ability to inhibit cell growth and is an important potential target for anti‐GC treatments.…”
Section: Discussionmentioning
confidence: 79%
“…MiR-592 has been reported to promote the progression, metastasis, and proliferation of human colorectal cancer cells [44] and the proliferation of prostate cancer cells [45]. Studies have also shown that the expression levels of PGD2 and PTGDR can influence Th2 cell proliferation in allergic inflammation [46], and that Prostaglandin D synthase and PGD2 can decrease gastric cancer cell proliferation [47]. Therefore, the results regarding the positive role of miR-592-5p in enhancing the proliferation of hippocampal neurons are consistent with those of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…HPGDS catalyzes the conversion of PGH 2 to PGD 2 , and closely related to the progression of inflammation. Although its role in breast cancer is not entirely clear, it is reported that HPGDS suppress gastrointestinal cancer progression [63,64]. However, molecular docking result showed that LF triterpenoids (except for For other targets including annexin A5 (ANXA5), prothrombin (F2) and renin (REN), there was no firm evidence to link their functions directly to breast cancer progression, and they were less significant in the PPI network, which meant that they might be not important targets for LF triterpenoids.…”
Section: Other Targetsmentioning
confidence: 99%